ANALYSIS STUDENTS' CRITICAL THINKING THROUGH AI-BASED SYNTAX - Maria Rosa Mistika Sato; Annisa Suci, Nur; Hidayah Tullah. S, Nur; Rampeng (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Important concerns regarding the calibre of students' writing and thinking have been brought up by the quick use of artificial intelligence (AI) techniques in higher education. When utilised thoughtfully and purposefully, AI-based syntactic tools like huge language model helpers can act as beneficial scaffolds for the development of critical thinking rather than acting as a shortcut for copying and pasting. study looks at how students in the English Education Study Program strengthen their critical thinking skills in relation to the use of AI-based syntax. design was used. The 2022 and 2023 cohorts, twenty-four students took part in semi-structured interviews, classroom observations, and document analysis of their writing assignments. The interactive model of data reduction, display, and conclusion drawing was used to analyse the data. The results show three main trends: students who used AI passively showed little metacognitive awareness; students who engaged analytically with AI-generated syntax showed stronger argument organization and sentence-level precision; and students who were guided to compare, evaluate, and revise AI outputs developed more reflective writing habits. The study comes to the conclusion that while AI-based syntactic tools do not automatically generate critical thinking, they can enhance students' reasoning, revision, and language assessment skills when integrated into structured educational activities. The pedagogical ramifications are examined for instructors who want to use AI as a tool for academic literacy rather than as a substitute for hard work.